Larvul Ngabal and Ain ni Ain as a Unifying Pluralism in the Islands Kei Southeast Maluku - Yudit Tiwery, Weldemina (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTIndonesia is a country that consists of various cultures, tribes, languages and religion. The plurality possessed is valued as the power to build the harmony of life among the citizens. There are many types of cultures that serve as the basis for living together by communities in each region, one of them is in Kei Islands, Southeast Maluku. People in Kei Islands, Southeast Maluku has local wisdom known as Larvul Ngabal and Ain ni Ain. These two local wisdoms become the unifying force of pluralism for the people in Kei islands that has been passed down from generation to generation. This study was conducted using qualitative method with descriptive data analysis. The purpose of this study was to find out the role of customary law of Larvul Ngabal and Ain ni Ain’s philosophy bringing together plurality in the Kei Islands, Southeast Maluku and its relevance to the peace building in Indonesia. The results showed that both local wisdom can unify plurality in Kei Islands, Southeast Maluku and has been used as a basis for living together.Keywords : Larvul Ngabal, Ain Ni Ain, Plurality, Kei Islands, Southeast MalukuABSTRAKIndonesia merupakan negara yang terdiri dari berbagai macam budaya, suku, bahasa dan agama. Kemajemukan yang dimiliki dihargai sebagai kekuatan untuk membangun kehidupan yang harmonis antar warga masyarakat. Terdapat banyak jenis budaya yang dijadikan sebagai dasar untuk hidup bersama oleh masyarakat di masing-masing daerah, salah satunya di Kepulauan Kei, Maluku Tenggara. Masyarakat di Kepulauan Kei, Maluku Tenggara memiliki kearifan lokal yang dikenal dengan nama Larvul Ngabal dan Ain ni Ain. Dua kearifan lokal ini menjadi kekuatan pemersatu kemajemukan bagi masyarakat di Kepulauan Kei yang telah terwariskan dari generasi ke generasi. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan analisa data deskriptif. Tujuan penelitian ini adalah untuk mengetahui peranan hukum adat Larvul Ngabal dan falsafah Ain ni Ain dalam mempersatukan kemajemukan di Kepulauan Kei, Maluku Tenggara dan relevansinya bagi pembangunan perdamaian di Indonesia. Hasil penelitian menunjukkan bahwa kedua kearifan lokal tersebut dapat mempersatukan kemajemukan di Kepulauan Kei, Maluku Tenggara dan telah dijadikan sebagai dasar untuk hidup bersama.Kata kunci: Larvul Ngabal, Ain ni Ain, kemajemukan, Kepulauan Kei, Maluku Tenggara